Sensory Attribute Properties and Shelf Life Of Chicken-Herbal Essence Functional Drinks - Puspasari, Erna; Sulaeman, Ahmad; Palupi, Eny; H. Pasaribu, Fachriyan; Apriantini, Astari (Universitas Airlangga, 2024)
Chicken-herbal essence, a nutritionally rich functional beverage boasting elevated levels of proteins and amino acids, is renowned for its health-promoting attributes, notably its positive effects on lactation. Comprising an amalgamation of free-range chicken, red ginger, brown sugar, honey, sesame oil, nutmeg, salt, and water, this elixir undergoes a discernible deterioration in quality when subjected to prolonged storage. Consequently, imperative research endeavors are undertaken to elucidate the temporal constraints of storage for this esteemed functional drink. The present study is oriented towards gauging the degradation in quality and prognosticating the shelf life of chicken-herbal essence when exposed to three distinct temperatures”refrigerator temperature (10°C), ambient room temperature (25-27°C), and an elevated temperature (35°C)”utilizing the Arrhenius method as the analytical framework. Conducted over a rigorously observed four-week duration at both the Djuanda University Food Laboratory and the LPPOM MUI Laboratory, this study systematically examines diverse parameters, including pH levels, total dissolved solids, total plate count (TPC), and a comprehensive sensory evaluation. The pH testing, conducted employing a precision pH meter, yields a range of 4.676 – 5.074, while total dissolved solids ranged from 27,100 – 27,450 Brix; total plate count ranged from 0 – 20 CFU/mL. In the sensory test, samples at three temperatures were withdrawn upon panelists' arrival. Generally, refrigerated and room temperature storage showed higher acceptability than higher temperature (35°C) storage. Shelf life estimation indicated that refrigerated storage (10°C) extended to 53 days, surpassing the other temperatures.